Mechanism of Action of Coumarin against Candida albicans by SEM/TEM Analysis - Gunawan Pamudji Widodo; Elin Yulinah Sukandar; I Ketut Adnyana; Sukrasno Sukrasno (Institute for Research and Community Services (LPPM) ITB, 2012)
The aim of this study was to identify the antifungal activity of coumarin isolated from Ageratum conyzoides L. leaves and to observe its influence on Candida albicans cells by scanning electron microscope (SEM) and transmission electron microscope (TEM). Antifungal activity testing with the disk diffusion method showed coumarin was active toward pathogenic fungus Candida albicans with an MIC value of coumarin of 125 ïg mL-1. The results show that this compound damaged the cell by pores formation on the cell wall. Death of cells occurred due to leakage and necrosis of cytoplasmic content.